Charcot neuroarthropathy of the knee due to idiopathic sensory peripheral neuropathy - Qian-Hao Yang; Peichun Hsu; You-Shui Gao; Chang-Qing Zhang (BMC Musculoskeletal Disorders, 2019)
Abstract Background Charcot neuroarthropathy is a systemic disease that generates pathological changes in the musculoskeletal system, causing instability, dislocations, and deformities. Charcot neuroarthropathy of the knee, due to either diabetes mellitus or syringomyelia, is anecdotally reported with the epidemic of the diseases. However, idiopathic sensory peripheral neuropathy can inflict osteoarticular structures directly, inducing a dysfunctional Charcot neuroarthropathy. An early diagnosis and effective relief of the symptomatic deformity is essential for the treatment. Case presentation We report the case of a patient with idiopathic sensory peripheral neuropathy who presented with a swelling right knee, as well as distorted and painless gait disorder, diagnosed as Charcot neuroarthropathy of the knee. Partial weight bearing with a hinged knee brace was used to correct the abnormal alignment and gait posture, and bisphosphonates were prescribed to decrease pathological bone resorption. Although the alignment and Knee Society Score got a gradual deterioration, the combination of orthosis and pharmacy could alleviate the symptom to a certain extent. Conclusion The diagnosis of Charcot neuroarthropathy of the knee is rare that requiring early diagnosis. The presence of features, including painlessness, numbness, and deformed arthropathy following chronic-onset algesthesia loss should be taken carefully.